Surface functionalization of nanostructured Cu/Ag-deposited polypropylene fiber by magnetron sputtering - Chu Changliu (De Gruyter, 2021)
The Cu/Ag nanostructured film that follows Volmer–Weber growth pattern was successfully deposited onto PP fiber surface using the magnetron sputtering technique.